Risk taking behaviour among urban and rural adolescents in two selected districts in Malaysia - Mohd N. Azmawati; Abdul H. Siti Hazariah; Azhar S. Shamsul; Ahmad Norfazilah; Noor A. Azimatun; Hod Rozita (South African Family Practice)
Background: Risk taking behaviour refers to the tendency to engage in behaviours that have the potential to be harmful or dangerous, which has become a major concern and is rated as one of the public health issues that need special attention. The objective of the study was to compare the prevalence of risk taking behaviour and its associated factors among urban and rural adolescents.